STUDENTS’ LEARNING OUTCOMES OF BLENDED LEARNING IMPLEMENTATION IN WRITING LESSON - Ayuni Madarina Abdul Rahman; Mohd. Nazri Latiff Azmi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
Writing requires specific skills in brainstorming, organizing, editing, and proofreading. There are varieties of research conducted in finding which approach is the most impactful to teach writing and one of the approaches emphasized is blended learning, widely acceptable in education field. Nevertheless, its effectiveness on writing is still questionable and the effort to integrate blended learning in teaching writing needs a thorough consideration. Therefore, the purpose of the study is to researcrh the adequacy of blended learning approach on students’ writing performance. Employing an explanatory research type, an experimental research design was applied. A mixed-method method was executed to collect, analyse and interpret data. For quantitative, a quasi-experimental design was carried out to 60 respondents who were selected through purposive samplings and distributed to control and experimental groups. The study used pretest and posttest for both groups. The result shows that there is no significant difference of blended learning and students’ writing performance between the experimental group and control group in the pretest and posttest. Overall, the study shows that both instructions have place in writing. Hence, educators have to become eclectic practitioners who are able to apply suitable approach that can contribute to the growth of teaching and learning writing.